Cord blood buffy coat DNA methylation is comparable to whole cord blood methylation. Issue 1 (2nd January 2018) - Dou, John; Schmidt, Rebecca J.; Benke, Kelly S.; Newschaffer, Craig; Hertz-Picciotto, Irva; Croen, Lisa A.; Iosif, Ana-Maria; LaSalle, Janine M.; Fallin, M. Daniele; Bakulski, Kelly M.
ABSTRACT: Cord blood DNA methylation is associated with numerous health outcomes and environmental exposures. Whole cord blood DNA reflects all nucleated blood cell types, while centrifuging whole blood separates red blood cells, generating a white blood cell buffy coat. Both sample types are used in DNA methylation studies. Cell types have unique methylation patterns and processing can impact cell distributions, which may influence comparability. We evaluated differences in cell composition and DNA methylation between cord blood buffy coat and whole cord blood samples. Cord blood DNA methylation was measured with the Infinium EPIC BeadChip (Illumina) in eight individuals, each contributing buffy coat and whole blood samples. We analyzed principal components (PC) of methylation, performed hierarchical clustering, and computed correlations of mean-centered methylation between pairs. We conducted moderated t-tests on single sites and estimated cell composition. DNA methylation PCs were associated with individual ( P PC1 = 1.4 × 10 −9 ; P PC2 = 2.9 × 10 −5 ; P PC3 = 3.8 × 10 -5 ; P PC4 = 4.2 × 10 -6 ; P PC5 = 9.9 × 10 -13, P PC6 = 1.3 × 10 −11 ) and not with sample type ( P PC1-6 >0.7). Samples hierarchically clustered by individual. Pearson correlations of mean-centered methylation between paired samples ranged from r = 0.66 to r = 0.87. No individual site significantly differed between buffy coat and whole cord blood when adjusting for multiple comparisons (five sites had unadjusted P <10 −5 ). Estimated cell type proportions did not differ by sample type ( P = 0.46), and estimated proportions were highly correlated between paired samples (r = 0.99). Differences in methylation and cell composition between buffy coat and whole cord blood are much lower than inter-individual variation, demonstrating that both sample preparation types can be analytically combined and compared.